2009
DOI: 10.1007/s00025-009-0437-2
|View full text |Cite
|
Sign up to set email alerts
|

Pasting Lemmas and Characterizations of Boundary Regularity for Quasiminimizers

Abstract: Quasiharmonic functions correspond to p-harmonic functions when minimizers of the p-Dirichlet integral are replaced by quasiminimizers. In this paper, boundary regularity for quasiminimizers is characterized in several ways; in particular it is shown that regularity is a local property of the boundary. For these characterizations we employ a version of the so called pasting lemma; this is a useful tool in the theory of superharmonic functions and our version extends the classical pasting lemma to quasisuperhar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Note that semiregularity and semiregularity for quasiminimizers coincide, by Björn [8]. For more on boundary regularity for quasiminimizers see Ziemer [31], J. Björn [18], Martio [28], Björn [5,8,9], Björn-Björn [10] and Björn-Martio [17].…”
Section: Theorem 26 (The Wiener Criterion) the Point X 0 ∈ ∂ω Is Rementioning
confidence: 98%
“…Note that semiregularity and semiregularity for quasiminimizers coincide, by Björn [8]. For more on boundary regularity for quasiminimizers see Ziemer [31], J. Björn [18], Martio [28], Björn [5,8,9], Björn-Björn [10] and Björn-Martio [17].…”
Section: Theorem 26 (The Wiener Criterion) the Point X 0 ∈ ∂ω Is Rementioning
confidence: 98%
“…Regularity for quasiharmonic functions was called regularity for quasiminimizers in Björn-Martio [15]. In Björn [6], it was shown that if u and f are as above and x 0 is strongly irregular for quasiharmonic functions, then, in our terms, f (x 0 ) ∈ C(u, x 0 , ).…”
Section: Boundary Regularity For Quasiharmonic Functionsmentioning
confidence: 96%
“…In Björn-Martio [15], the following characterization was given. It was also observed there that it holds if "quasi" is replaced by "Q-quasi" throughout.…”
Section: Theorem 72 (Weak Kellogg Property For Quasiharmonic Functiomentioning
confidence: 98%
See 1 more Smart Citation
“…Most aspects of the higher-dimensional theory fit just as well in metric spaces, and this theory, in particular concerning boundary regularity, has recently been developed further in a series of papers by Martio [17]- [19], A. Björn-Martio [7], A. Björn [1]- [4] and J. Björn [9].…”
Section: Introductionmentioning
confidence: 99%